Competitive Intelligence in the Tourism Sector, with special focus on Southern Europe - Gisela Casado Salguero; José A. Jiménez Quintero (Tourism & Management Studies)
The current organisational environment is characterised by rapid change. This means that if businesses want to survive, they must stay abreast of these changes so as to take the most appropriate and riskminimizing decisions. This can only be done if the decision makers have access to Intelligent Information. To obtain this information, it is necessary to have structured processes of Competitive Intelligence in place. Large businesses have been doing this for years, and now more and more small and mediums business are doing it too. In this paper, an analysis will be carried out of the implementation of these Competitive Intelligence processes in hotels in the Costa del Sol - a valued beach holiday destination on a European level. Despite strong competition from other such destinations, the Costa de Sol attracts millions of sun-seeking holiday-makers, as well as more and more visitors from other tourism sectors, such as sport and culture.